Assessing the limiting factors of natural regeneration in Mediterranean planted hedgerows - García de León, David; Rey Benayas, José M.; Villar-Salvador, Pedro (Frontiers in Ecology and Evolution, 2023)
Conservation and restoration of hedgerows promote biodiversity and multi-functionality in agricultural landscapes. However, in Mediterranean environments, natural regeneration of hedgerows is often poor, and factors hindering the establishment and growth of hedgerow woody species remain unclear. This study aimed to address this gap by (1) quantifying natural regeneration, including seedling establishment and resprouting of planted hedgerow species and the establishment of woody species coming from outside the hedgerows; and (2) experimentally assessing the impact of drought, herbivory, and herb competition on seedling establishment. We selected 12 planted, 11–13-year-old hedgerows in four sites in Central Spain to sample their natural regeneration. In addition, we transplanted 1,356 seedlings of Colutea arborescens L., Crataegus monogyna Jacq. and Rhamnus alaternus L. to two field sites under three treatments that were applied factorially for two years: irrigation to alleviate summer drought, protection against herbivory, and herb clipping to reduce competition with transplanted seedlings. We found that only 66 juveniles of woody species, including 29 of species that were not planted in the hedgerows, developed from seed germination, and 316 sprouts recruited spontaneously along 10 years (14 individuals ha−1 year−1). Of the transplanted seedlings, only 22% survived after two years with protection against herbivory strongly enhancing seedling survival. To a lesser extent, irrigation and herb competition affected survival through interactions with herbivory and species identity. Irrigation and protection against herbivores accelerated seedling growth. Survival and growth of C. arborescens (14%; seedling height = 12 ± 9 cm) were lower than those of C. monogyna (41%; 21 ± 11 cm) and R. alaternus (17%; 13 ± 8 cm). We conclude that natural regeneration in Mediterranean planted hedgerows is low, herbivory is the main limiting factor for seedling survival, especially for deciduous species, and summer drought and herb competition mostly limit growth. These findings have important implications for the conservation and restoration of hedgerows in Mediterranean environments.